Language styles variation in an Islamic boarding school: Sociolinguistic study and EFL implications - Rizki Ba’da Mauludiyah; Dhea Syahzana Sahreebanu; Mirjam Anugerahwati; Evynurul Laily Zen (English Learning Innovation, 2025)
The present study examines the use of language styles among santri (students studying and living in an Islamic boarding school) in one of Islamic boarding schools located in East Java, Indonesia. Referring to Joos’ (1967) five language styles and Allan Bell’s Audience Design Theory (2014), this study explores how santri adjust their speech styles based on social context and interlocutors, particularly when interacting with peers, seniors, and ustadzah (female teachers who teach Islamic studies). Using semi-structured interviews and direct observation involving nine participants from grades seven to nine, thematic analysis revealed six main themes, notably adaptation to hierarchical relationship and strategic code-switching between Indonesian and Javanese to manage formality. Findings indicate that casual style dominates peer interactions, while consultative and formal styles are often used to communicate with seniors and ustadzah, often incorporating Javanese and Indonesian polite forms. Emotional and situational factors, such as when managing conflict and showing empathy also influence language choice. This study highlights santri’s strong sociolinguistic awareness and suggests their ability to adapt speech in L1 can be utilized to enhance sociolinguistic competence in EFL (English as a foreign language) context.